Use of Frontal Sinus Morphometric Analysis by Computerized Tomography in Sex Determination - Ekizoğlu, Oğuzhan; Hocaoğlu, Elif; İnci, Ercan (The Bulletin of Legal Medicine, 2017)
Abstract Objective: The aim of the this study is to evaluate usefulness of results of measurements via computerized tomography of frontal sinus dimensions in sex determination. Materials and methods: In Bakirkoy Training and Research Hospital subjects who had performed maxillofacial computed tomography were included. Transvers diameters (width) were measured from axial images, anterior-posterior (depth) and cephalo-caudal diameters (height) were measured from sagittal reformatted images. Measurements were performed for both left and right frontal sinuses. The size of frontal sinuses on both sides were obtained using these parameters. These values were evaluated with independent t test .The variables were evaluated discrimination function analysis Results: For study 400 subjects were evaluated (200 male and 200 female). 400 case (female/male: 200/200, mean age: 30.12 ± 10.2) All values for left and right transvers, cephalo-caudal and antero-posterior measurements showed significant difference between sex. Male sex had significant increased valued then female sex. (p<0.001) In single discrimination analysis the lowest accuracy rate was 55.5% for LH in the male, and 59.5% for RT in female. Highest accuracy rates were observed are LAP (77.5%) and RAP (77%) in female and LAP (69%) in male. when only the RAP and LAP values were added the accuracy rate was detected as 77.5% in female and 70.5% in male. If all measured values included in the stepwise discrimination analysis the accuracy rate was detected as 80.5%% in female and 71.5% in male. Conclusion: The frontal a sinus morphometric studies, particularly in multicultural societies, can provide important data for research. The data will be useful for forensic specialists and anthropologists, as well as craniofacial surgeons and dentists who perform endoscopic and surgical procedures in related anatomical structures. Keywords: Frontal sinus, sex determination, computerized tomography